A critical review of international research into pre-service teachers' beliefs and practices when teaching migrant learners (UCL Press, 2023)
This article provides a critical qualitative review of 26 English-language journal articles from multiple countries that focus on research and practice among pre-service teachers, and their beliefs about, and experiences of, teaching migrant learners. The findings are organised around two themes. First, the review reveals that student teachers are more likely than not to hold negative beliefs and harbour anxieties about teaching migrant learners. While the cultural diversity of the country in which the student teachers are working does not seem to be a strong determinant of such beliefs, research suggests that such beliefs are more often linked to a lack of knowledge and training. Second, the review identifies a strong emphasis on belief in the value of empathy in learning to teach migrant learners, with the caveat that having a migrant background does not necessarily lead to a more empathetic student teacher. The wider discussion problematises empathy as a goal of training and highlights the challenges inherent in encouraging the development of critical self-reflection among pre-service teachers. The review ultimately questions the extent to which pre-service teacher education equips pre-service teachers to work effectively with migrant learners and proposes increased collaborations between researchers and pre-service teachers as a step towards expanding critical research and practice.